Reordenamento de redes escolares no Brasil e em Portugal : racionalizar para qualificar para o ensino? - Graça, Tereza Cristina Cerqueira da (2016)
This thesis investigates the school systems rearrangement processes in Brazil and Portugal, as a way of coping with enrollment drops in primary and secondary education due to the falling birth rates from 2002 to 2012. The hypothesis is that the rearrangements of school systems compasses the rationalization of education and are encouraged by multilateral funding agencies. The research uses the categories of analysis from comparative education, which includes authors such as BRAY and KAI (2010), GARRIDO (1997), MANZON (2010), NÓVOA and CATANI (2000), SCHRIEWER (1990, 1995, 2010), SOUZA and MARTINEZ (2009), as well as other Brazilian and Portuguese scholars, like ANTUNES (2005), AKKARI (2011), BOMENY (2001), CASTRO (2013), RIBEIRO (2008), SANTOS (2011), STOER ( 1980, 1999), THEODORO (2008). Data and information were gathered from government offices, newspapers and academic studies. In Brazil, we focus on the rearrangements occurred in the Northeastern States, furthering some approaches with some other Brazilian States; in Portugal, we analyse a few “CartasEducativas” from some representative cities of each Portuguese geographic regions. The historical path of Education explains the late universalization basic education, illiteracy and low rates of education of the population. Low use of public school buildings and the reduction of the number of students led both countries to foster their school systems rearrangements through various procedures and strategies, which greatest impact is still schools closure. In Portugal, the rearrangements led to the constitution of school groups, and in Brazil to the expansion of the daily school. In both countries, these processes are taking place paripassu a process in which cities are taking control over primary education – but in Brazil, this process is in a more advanced stage because of the federative model of government. Relations between central and local powers and those with educational segments, the relations between private and public schools, the different influence levels of international organizations and the progress accomplished in education are analyzed in order to identify the contribution of schools systems rearrangements in schooling expansion and improvement of educational services. In Portugal, the findings indicate that the school system rearrangement is part of the government commitments to reduce the public expenditure made by the country with international organizations. In Brazil, where this process is very recent, this intervention is motivated by the disclosure of the international experiences. With no demographic surveys or researches, as well as no medium or long-term planning, the school systems rearrangements are going on as long as some public schools are being emptied due to reducing rates of students. Given the demographics and urban reconfigurations, the public school systems rearrangements are needed, and undoubtedly part of the public funds rationalisation policies announced / implemented by successive governments. However, this process lacks transparency and openness to the engagement of some educational segments.